RANCANGAN PERBAIKAN MEJA KERJA DENGAN METODE QUICK EXPOSURE CHECK (QEC) DAN ANTROPOMETRI DI PABRIK TAHU SUMEDANG - Siboro, Benedikta Anna Haulian; Sofian, Rahmat; Purbasari, Annisa (Sekolah Tinggi Teknologi Adisutjipto, 2016)
Soaking and cleaning raw material soybeans is one of manual material handling of tofu proces. In this process, operators lift the water with a hunched position, regardless of their health, comfort, and safety, then finally will impact to lower back pain.This research aims to design a ergonomic table of raw materials soybean based on anthropometry operators by Quick Exposure Check at UKM Tahu Sumedang. The data collection is done by field studies, interviews with workers, such as questionnaires and anthropometric data for example posture of workers that covers the back, arms / shoulders, wrists, and neck to do data processing using QEC method (quick exposure check).The result is shown that the average percentage of exposure level for six workers was 72% that need action to be taken, namely improvement of working table. The design size of working table using ergonomic wastafel principles which anthropometric measurements for arm = 67.01 cm, long-range hand = 167.30 cm, standing elbow height = 122.94 cm. The percentage of QEC after improvement is decrease become 36%, it means design can reduce complaints and taste below the maximum % QEC (40%)Kata kunci: work posture, QEC, anthropometry, wastafel table